Development of A Nurse-Led Educational Intervention Program in Managing the Nutrition Impact Symptom Cluster in Patients with Nasopharyngeal Carcinoma following the Medical Research Council Framework - Wenli Xiao; Carmen WH Chan; Jinnan Xiao; Cho Lee Wong; Ka Ming Chow (Elsevier, 2021)
Objective: This article aimed to report the experience of developing a complex nurse-led, theory-driven, and evidence-based educational intervention program intended to manage the nutrition impact symptom cluster experienced by patients with nasopharyngeal carcinoma (NPC) during radiotherapy, based on the Medical Research Council (MRC) framework. Methods: The "development" and "feasibility and piloting" phases of the MRC framework were used to guide the intervention development. The development phase included identifying the evidence base through a systematic review, exploring the relevant and guiding theory to enhance the effectiveness of the intervention and conducting a qualitative study to identify the intervention modelling. For the feasibility and piloting phase, we conducted a pilot study to examine the feasibility and estimate the effectiveness of the intervention. Results: The systematic review revealed that nurse-led educational interventions were used commonly for symptom cluster management, with promising effectiveness. The theoretical foundation was provided by the Theory of Unpleasant Symptoms, which indicates that an educational intervention can help patients to manage symptom cluster by influencing psychological, situational, and physiological factors. The qualitative study further provided contents of the intervention based on the perspectives of NPC patients and health professionals. The resulting program involves a nurse-led, family caregiver involvement, educational intervention with two sessions that uses a booklet as a medium. The pilot study found that conducting the educational intervention program was feasible and it also had some favorable effects on managing the nutrition impact symptom cluster in NPC patients. Conclusions: The MRC framework provided a strong structure with which to develop a complex intervention for nutrition impact symptom cluster management through a theory-driven and evidence-based approach. The evaluation of the intervention, the delivery process and the mediation mechanism of change using a rigorous randomized controlled trial design is recommended.